A PORTRAIT OF DEVELOPMENT IN W.S. RENDRA’S POEM BLUES FOR BONNIE - Haryadi; Ismail, Gunawan; Sulistyo, Bambang (Prosiding Konferensi Internasional Kesusasteraan, 2025)
This research aimed to analyze the interrelation between literature, education, and social movements through a case study of the poem Portrait of Development in the Poem: Blues for Bonnie by WS Rendra. The research method used in this study was descriptive qualitative analysis with a sociological literary criticism approach. Data were obtained through close reading, data classification, analysis of the socio-historical context, interpretation of meaning, and synthesis of findings from the poem’s text, as well as the expansion of its social-political context during the time of its creation. The findings indicate that WS Rendra’s poem functions not only as an aesthetic expression but also as an educational medium that raises public awareness of issues related to development and injustice. By portraying critical social conditions, the poem stimulates reflection and encourages social movements for change. This critique is conveyed through diction, imagery, figurative language, and stylistic choices that illustrate social inequality and dehumanization resulting from development. The conclusion of this research is that literature, particularly poetry, holds great potential as a transformative tool that connects education and the awakening of social consciousness, which in turn can contribute to broader social change.